The safety of activated eptacog beta in the management of bleeding episodes and perioperative haemostasis in adult and paediatric haemophilia patients with inhibitors. Issue 6 (11th October 2021) - Escobar, Miguel; Castaman, Giancarlo; Boix, Santiago Bonanad; Callaghan, Michael; de Moerloose, Philippe; Ducore, Jonathan; Hermans, Cédric; Journeycake, Janna; Leissinger, Cindy; Luck, James; Mahlangu, Johnny; Miesbach, Wolfgang; et al.
Abstract: Introduction: Haemophilia patients with inhibitors often require a bypassing agent (BPA) for bleeding episode management. Eptacog beta (EB) is a new FDA‐approved recombinant activated human factor VII BPA for the treatment and control of bleeding in haemophilia A or B patients with inhibitors (≥12 years of age). We describe here the EB safety profile from the three prospective Phase 3 clinical trials performed to date. Aim: To assess EB safety, immunogenicity and thrombotic potential in children and adults who received EB for treatment of bleeding and perioperative care. Methods: Using a randomized crossover design, 27 subjects in PERSEPT 1 (12‐54 years) and 25 subjects in PERSEPT 2 (1‐11 years) treated bleeding episodes with 75 or 225 μg/kg EB initially followed by 75 μg/kg dosing at predefined intervals as determined by clinical response. Twelve PERSEPT 3 subjects (2‐56 years) received an initial preoperative infusion of 75 μg/kg (minor procedures) or 200 μg/kg EB (major surgeries) with subsequent 75 μg/kg doses administered intraoperatively and post‐operatively as indicated. Descriptive statistics were used for data analyses. Results: Sixty subjects who received 3388 EB doses in three trials were evaluated. EB was well tolerated, with no allergic, hypersensitivity, anaphylactic or thrombotic events reported and no neutralizing anti‐EB antibodies detected. A death occurred during PERSEPT 3 and was determined to be unlikely related to EB treatment by the data monitoring committee. Conclusion: Results from all three Phase 3 trials establish an excellent safety profile of EB in haemophilia A or B patients with inhibitors for treatment of bleeding and perioperative use.